Exploiting trypanosomes as models for pathogenicity and core biology research - Awuah-Mensah, Georgina (2021)
Model systems are commonly used to investigate biological processes and understand molecular mechanisms. The choice of a model cell or organism is informed by the scope of the question being asked. Decades of research using predominantly animal and fungal models form the bulk of our knowledge of eukaryotic processes. The diversity of eukaryotic organisms, however, indicates that this may not be representative of what exists in more diverged groups, and key processes like cell division vary across the larger group. In the past, non-traditional models including Tetrahymena have been applied to answer biological questions because of peculiar traits that make them suitable for investigation. African trypanosomes offer an excellent opportunity as model organisms because of their divergence from common models and importance to human health and livelihood. Particularly Trypanosoma brucei, with several genetic tools available to study them, has become an interesting model to study processes like cell division, cytoskeleton and antigenic variation. Here, I present work exploring the application of two species of African trypanosomes as models to investigate common biology of eukaryotic kinesins and specific biology of animal African trypanosomiasis.